TRANSLATION ACCURACY OF ENGLISH COMPLEX SENTENCE INTO INDONESIAN IN THE NOVEL OF “JULIET” BY ANNE FORTIER - Nur Shofa Azzahra; Ruminda Ruminda (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Translation has contributed a huge effect to everyday life since its existence. The translation is a very complex language activity that requires the translator to have knowledge on language and grammar, at the same time culture, social, religion, and material. The purpose of this study is to assess the translation accuracy of English complex sentences into Indonesia in a novel entitled “Juliet” written by Anne Fortier using the theory of Nababan’s translation accuracy assessment. The novel is the most dominant literary work to read. Nowadays, there are a lot of novels have been translated into various languages. It contains various sentence structures, and the structure should be translated well. The complex sentence has a complex and challenging structure. The method used in this study is qualitative. 52 data are collected and ranged from 1 to 3, depending on their accuracies. The higher the score shows, the more accurate translation; and the lower the score, the less accurate translation. The result showed that the translations are accurate, with a score of 2,7.